2006
DOI: 10.1029/2006gl027235
|View full text |Cite
|
Sign up to set email alerts
|

Transoceanic wave propagation links iceberg calving margins of Antarctica with storms in tropics and Northern Hemisphere

Abstract: We deployed seismometers on the Ross Ice Shelf and on various icebergs adrift in the Ross Sea (including B15A, a large 100 km by 30 km fragment of B15, which calved from the Ross Ice Shelf in March, 2000). The data reveal that the dominant energy of these floating ice masses is in the 0.01 to 0.1 Hz band, and is associated with sea swell generated in the tropical and extra‐tropical Pacific Ocean. In one example, a strong storm in the Gulf of Alaska on 21 October 2005, approximately 13,500 km from the Ross Sea,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 22 publications
4
117
0
Order By: Relevance
“…The AIS has long been considered a stable ice shelf that is currently undergoing a natural advance-calve-advance cycle (Fricker et al, 2002). Observations of its mass balance (Wen et al, 2006(Wen et al, , 2008Yu et al, 2010) and model studies of the rift propagation process on its ice front (Larour et al, 2004;Bassis et al, 2005;MacAyeal et al, 2006) support that hypothesis. But the future state of the whole drainage system has large uncertainties under the influence of global warming and model studies can perhaps throw light on the future of the ice shelf and its adjacent glaciers.…”
Section: Introductionmentioning
confidence: 53%
“…The AIS has long been considered a stable ice shelf that is currently undergoing a natural advance-calve-advance cycle (Fricker et al, 2002). Observations of its mass balance (Wen et al, 2006(Wen et al, , 2008Yu et al, 2010) and model studies of the rift propagation process on its ice front (Larour et al, 2004;Bassis et al, 2005;MacAyeal et al, 2006) support that hypothesis. But the future state of the whole drainage system has large uncertainties under the influence of global warming and model studies can perhaps throw light on the future of the ice shelf and its adjacent glaciers.…”
Section: Introductionmentioning
confidence: 53%
“…However, the probability an iceberg will calve during a given interval of time can be described 30 by a probability distribution. This probability distribution depends on environmental conditions that can stimulate or inhibit the fracturing mechanism (MacAyeal et al, 2006). If the environmental parameters conditioning the probability of fracture can be determined, it would thus be possible to propose at least bulk fracturing laws that could be used in numerical models.…”
Section: Fragmentation Lawmentioning
confidence: 99%
“…Several authors have suggested that calving from ice shelves and ice tongues may be triggered by flexural stresses induced by ocean swell (Holdsworth & Glynn 1978;MacAyeal et al 2006;Sergienko 2010), despite some contradictory observations that ice shelf rift propagation itself is not influenced by ocean swell (Bassis et al 2007(Bassis et al , 2008. To examine the role of ocean swell in generating transient stresses that contribute to failure of floating ice tongues, we estimated the magnitude of the horizontal stress induced in the ice following the order of magnitude estimation procedure described by Bassis et al (2007Bassis et al ( , 2008.…”
Section: (D) the Role Of Ocean Swell In Triggering Calving Events Fromentioning
confidence: 99%